Psychosocial Adjustment Among Senior Volleyball Players in Libya - Belaid, Mabrouk Faraj Wanis; Jalid, Mohamed Chadli (Advances in Social Sciences Research Journal, 2024)
The research aimed to identify the level of psychosocial compatibility among senior volleyball players in Libya, and the research community consisted of (120) senior volleyball players distributed among (10) clubs, where the research was conducted by a comprehensive inventory method and the researcher used the Cooper-Smith scale (1978) and the Watkins scale (1978) to measure psychological compatibility, The reliability and Reliability of the study tool was verified using statistical methods represented by arithmetic means, standard deviations, percentages and inferential statistics to test the Reliability of the study tool (Pearson correlation coefficient, Cronbach's alpha) and in light of the research results a set of recommendations, including working on Training in the psychological field by collecting scientific information in psychology and social psychology and the necessity of having a psychologist in the teams in order to help them deal with various situations in their sports life and help players overcome the difficulties that may meet them that are consistent with their inclinations and desires.